Prospects of the Development of the International Law in the XXI century - S. V. Bakhin (Московский журнал международного права)
On October 18-19, 2007 in Saint-Petersburg there was hold a Conference “Prospects of the Development of the Legal Regulation of International Relations in the XXI century”. Simultaneously the birthday of Prof. Lyudmila Nikiforovna Galenskaya, the Professor of the Chair of International Law of the Law faculty of the Saint-Petersburg State University, was celebrated. The Conference focused both on public and private international law aspects Many issues and problems of contemporary international law were covered and discussed. Prof. Galenskaya in her speech focused on the tendencies of the development of the international law and international relations, pointing out three major factors affecting these phenomena: globalization, technological progress and ecology. The presentations that followed touched upon different aspects of international law and offered an insightful analysis of the issues which are acute for the contemporary world. Among of the questions which were actively discussed were the issues of private international law, international security, law of the sea, regime of the territories, legal regulation of the economic sphere, etc. At the end of the Conference each participant was presented with a book “International Public and Private Law: problems and prospects. Liber amicorum in honour of Professor L.N. Galenskaya”.